Low grade energy engines - Mohey El-Din, K. H. (Cranfield University, 1981)
It is clear that there is no long-term solution to energy supply problems other than planned and continuous conservation. The use of low-grade energy as an unlimited resource will play an important part in maintaining the balance between the future of the world for both developed and developing countries alike. energy supply and demand A literature survey reviewing the most , the construction of low-grade energy engines has been conducted. The V promising approaches to' validity of each feasible system has been examinéd and the of operation described principles cycle utilizing common suitable refrigerants (e.g. halo-carbons) as A feasibility study concerning the adoption_of the organic Rankine ` working fluids has been conducted. In particular, the use of a multiple vane expander as the prime mover has been A suite of computer programs has been developed to fully investigated; describe working fluid properties optimise the geometrical and dynamical parameters of the Rankine cycle to achieve the most efficient operation in both steady and`transient states ' ' optimise the mechanical design of the expander depending upon the mode of operation and-the source and sink characteristics ' fully flexible experimental test facility was constructed so ., as to be capable of testing a wide variety of prime movers. This has _ been operated for a real time test period in excess of 300 hours. ` The test results are encouraging. Efficiencies were measured V in_accordance with the mathematical predictions and a portfolio of - and_reliable expander capable of utilising low has been produced. , Fruitful links with relevant have been forged. ,"Demonstrations of the system are planned the UK and overseas. L A ' ~ within British industries grade thermal energy suggested modifications towards a high efficiency, low-cost, robust